Ethical Leadership On Job Satisfaction: The Role Of Psychological Safety And Self-Efficacy - Yonatan Asadi Djaya; Eisha Lataruva; Ega Arminta (Eduvest - Journal of Universal Studies, 2024)
The change from the 2013 Curriculum to the Independent Curriculum means that teachers need to understand the role and function of teachers in implementing the Independent Curriculum. Understanding these roles and functions makes teachers feel satisfied in their work. This research aims to analyze the influence of Ethical Leadership on Job Satisfaction. This research was conducted on permanent teachers at five private high schools (SMA) in Semarang City. The population and sample in this study were all permanent teachers in five private high schools in Semarang City, totaling 180 people. The results of this study indicate that Ethical Leadership has no significant effect on Job Satisfaction, Ethical Leadership has a significant positive effect on Psychological Safety, Psychological Safety has a significant effect on Job Satisfaction, Psychological Safety mediates the relationship between Ethical Leadership and Job Satisfaction, and Self-Efficacy does not moderate the relationship between Ethical Leadership and Job Satisfaction.